Bio-based vitrimer-like polyurethane based on dynamic imine bond with high-strength, reprocessability, rapid-degradability and antibacterial ability. (26th October 2021) - Sun, Yinglu; Sheng, Dekun; Wu, Haohao; Tian, Xinxin; Xie, Haopu; Shi, Biru; Liu, Xiangdong; Yang, Yuming
Abstract: Synthesis of vitrimer with dynamic covalent bond is a surprising solution to overcome the inherent limitations of traditional thermosets. A bio-based vitrimer-like polyurethane formed by castor oil, vanillin, m-xylylenediamine and 4, 4′-dicyclohexylmethane diisocyanate in the preparation has superior mechanical properties, good solvent resistance, good thermal stability. Furthermore, the existence of dynamic imine bond in the vitrimer-like polyurethane is prone for polyurethane to rapid stress relaxation behavior, remoldability, weldability, antibacterial ability. With the hydrolysis of the imine bond, the material can be rapidly degraded at 60 °C for 1 h. In addition, it's commendable that the material exhibits excellent reprocessability that can be maintained at 86% even after 3 consecutive smash/mold pressing cycles. This work provides a promising method to manufacture bio-based polyurethane thermosets with excellent reprocessability, rapidly-degradable and antibacterial property, which has also promoted the high-value utilization of biomass materials. Graphical abstract: Image 1 Highlights: A novel bio-based vitrimer-like polyurethane containing castor oil and vanillin with high-strength has been synthesized. Imine exchange reaction in the networks exhibits fast relaxation behavior and thermal processability. The bio-based vitrimer-like polyurethane can be chemically degraded quickly under mild conditions. Antibacterial performance was verified with an antibacterial rate of up to 86.63%.